1994
DOI: 10.1111/j.1399-302x.1994.tb00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of cloned T helper cells ameliorates periodontal disease in nude rats

Abstract: We have previously described a T helper cell 2-type clone, A3, of rat T cells that provides help for antibody production to Actinobacillus actinomycetemcomitans in vitro and in vivo in normal (euthymic) isogeneic Rowett strain recipient rats. Adoptive transfer of this T helper cell clone to euthymic rats also protects them from periodontal bone loss induced by oral infection with A. actinomycetemcomitans. In the present study, to assess the cell requirement for protection, A3 clone T lymphocytes (10(6)) or nai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 26 publications
3
49
0
2
Order By: Relevance
“…It is not clear whether this difference indicates that B cells can contribute more extensively to bone resorption than T cells in the lesions. In our adoptive transfer studies Th2 cells ameliorated bone resorption and resulted in marked increased in Ab (12,28). In the more recent studies several Th1 Ag-specific clones gave rise to significant bone resorption that could be ablated with CTLA4-Ig and OPG-Fc (13,22).…”
Section: Discussionmentioning
confidence: 83%
“…It is not clear whether this difference indicates that B cells can contribute more extensively to bone resorption than T cells in the lesions. In our adoptive transfer studies Th2 cells ameliorated bone resorption and resulted in marked increased in Ab (12,28). In the more recent studies several Th1 Ag-specific clones gave rise to significant bone resorption that could be ablated with CTLA4-Ig and OPG-Fc (13,22).…”
Section: Discussionmentioning
confidence: 83%
“…We and others have shown that infection with live P. gingivalis predominantly elicits a Th1-type response in experimental animals and in humans [15]. In addition, adoptive transfer experiments have indicated an active role for Th1 cytokines in periodontal disease exacerbation, and some studies have shown that Th2 cytokines may be protective [9,16]. However, other studies suggest that this association is not consistently observed [17,18,19].…”
Section: Discusssionmentioning
confidence: 76%
“…A. actinomycetemcomitans infection is usually accompanied by local and systemic antigen-specific immune responses (18)(19). Earlier studies demonstrated altered CD4 + /CD8 + T-cell ratios and autologous mixed lymphocyte reactions in LJP patients (20,21) and the ability of T helper cells to home to periodontal tissues in rat and mouse models of periodontitis (22)(23)(24). Further, we have previously demonstrated that A. actinomycetemcomitans infection in NOD/SCID mice engrafted with human peripheral blood leukocytes (HuPBLs) leads to periodontal inflammation characterized by the infiltration of CD4 + T cells, CD8 + T cells, CD20 + B cells, and Mac1 + macrophages into the fibrous connective tissues adjacent to the periodontal pockets (24).…”
Section: Introductionmentioning
confidence: 99%